2022
DOI: 10.3390/antibiotics11030414
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Toothpastes Containing Natural Extracts on Bacterial Species of a Microcosm Biofilm and on Enamel Caries Development

Abstract: This study investigated the effects of herbal toothpaste on bacterial counts and enamel demineralization. Thirty-six bovine enamel samples were exposed to a microcosm biofilm using human saliva and McBain saliva (0.2% sucrose) for 5 days at 37 °C and first incubated anaerobically, then aerobically–capnophilically. The following experimental toothpaste slurries (2 × 2 min/day) were applied: (1) Vochysia tucanorum (10 mg/g); (2) Myrcia bella (5 mg/g); (3) Matricaria chamomilla (80 mg/g); (4) Myrrha and propolis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Less bacteria in the reformed biofilm were counted, and less surface microhardness loss was measured after brushing enamel specimens with the toothpaste supplemented with EEPg once per day over 14 days. This confirms another in vitro study where an herbal-propolis toothpaste prevented mineral loss [ 26 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Less bacteria in the reformed biofilm were counted, and less surface microhardness loss was measured after brushing enamel specimens with the toothpaste supplemented with EEPg once per day over 14 days. This confirms another in vitro study where an herbal-propolis toothpaste prevented mineral loss [ 26 ].…”
Section: Discussionsupporting
confidence: 88%
“…The initial retarding of biofilm formation might be of more clinical relevance than the result after 24 h, as tooth brushing twice per day is generally recommended [ 38 ]. Comparable studies cultured the biofilms for several days and applied in intervals the propolis toothbrush slurries [ 26 , 39 ]. In one study, propolis-containing toothpaste reduced more bacterial counts than one without active ingredients but less than one containing triclosan; the detailed analysis showed a suppression of S. mutans by the propolis toothpaste [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and Matricaria chamomilla L. in the toothpastes reduced the bacterial number in the microcosm biofilms. The enamel demineralization assay revealed that Vochysia tucanorum, Myrcia bella, Matricaria chamomilla, and Myrrha & propolis toothpastes reduced mineral loss and lesion depth compared with the placebo group (Braga et al, 2022). Another study demonstrated that natural products (including Commiphora myrrha resin extract, propolis extract) in the commercial toothpastes reduced microcosm biofilm viability and increased mineral loss (Braga et al, 2019).…”
Section: Effects Of Natural Products On Multi-species Biofilmsmentioning
confidence: 99%